The effect of Fifa 11+ injury prevention program on hamstrings and quadriceps isometric muscle strength in Iranian young professional soccer players - Hamid Reza Sadeghipour; Nader Rahnama Rahnama; Abdolhamid Daneshjoo; Effat Bambaeichi (Vesnu Publications, 2013)
Introduction: There is no surprise that the knee is the most common injured joints in soccer players. Also muscles strength is known as one of the most important factors for preventing muscle and ligament injuries. The aim of this study was to investigate the effect of FIFA 11+ injury prevention program on knee isometric muscle strength in young professional male soccer players. Materials and Methods: Isometric knee strength was assessed in twenty four professional soccer players. They classified equally into two experimental and control groups. Parameters were measured by Biodex (version 3) in 30°, 60°, and 90° knee flexion angles. Paired and Independent sample t-test, and two-way repeated measures ANOVA were used to analyze the data. Results: The results showed that the quadriceps' isometric strength in 90-degree was significantly higher in pre-test than post-test (P ≤ 0.05). Significant difference was observed in quadriceps' peak torque in control and experimental groups in 30 degree (P < 0.001), 60 degree (P ≤ 0.05), and 90 degree knee flexions (P ≤ 0.05). In experimental group, there is statistically significant between three knee flexion angles in quadriceps peak torque (P < 0.001), while maximum peak torque was found in 90 degree (303.6 N/m). Prominent differences in hamstrings' peak torque were seen between three knee flexion angles of experimental group (P < 0.001). Maximum torque produced by the hamstring muscles was discovered in 30 degree knee flexion (155.1 N/m). Conclusion: It can be concluded that the FIFA 11+ program could be an effective muscle strengthening training in young professional soccer players to improve knee muscles endurance and strength. It is recommended that more exercises program which aimed to increase hamstring strength such as hamstring curl should be added to FIFA 11+ training program. Keywords: FIFA 11+, Soccer, Hamstrings, Quadriceps